2015
DOI: 10.1093/ecco-jcc/jjv233
|View full text |Cite
|
Sign up to set email alerts
|

Switching Between Infliximab Originator and Biosimilar in Paediatric Patients with Inflammatory Bowel Disease. Preliminary Observations

Abstract: Switching from infliximab originator to its biosimilar seems to be a safe option in children with CD. After the switch the biosimilar was just as effective as the originator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 14 publications
7
95
0
Order By: Relevance
“…9,10 About 50% of patients with psoriasis who start infliximab have to discontinue treatment within the first year because of loss of efficacy attributed to antiinfliximab antibodies and a faster drug clearance.…”
Section: Cohort 1: Patients With Psoriasis Who Switched From the Inflmentioning
confidence: 99%
“…9,10 About 50% of patients with psoriasis who start infliximab have to discontinue treatment within the first year because of loss of efficacy attributed to antiinfliximab antibodies and a faster drug clearance.…”
Section: Cohort 1: Patients With Psoriasis Who Switched From the Inflmentioning
confidence: 99%
“…Switching from the infliximab originator to its biosimilar was also shown to be safe in pediatric CD patients, and appeared to be as effective as the originator [107,108].…”
Section: Biosimilars In Ibdmentioning
confidence: 97%
“…Nevertheless, there is no evidence to support true interchangeability, which requires the safe and tolerable switch from originator to biosimilar and back again. Recent studies of infliximab biosimilars indicated efficacy and safety similar to the infliximab originator [95][96][97]. Importantly, antibodies to infliximab also recognize biosimilar infliximab [98].…”
Section: Future Directions Inflammatory Bowel Diseasementioning
confidence: 99%